A Decade of Effective Dry Eye Disease Management with Systane Ultra (Polyethylene Glycol/Propylene Glycol with Hydroxypropyl Guar) Lubricant Eye Drops - Srinivasan S (Dove Medical Press, 2021)
Sruthi Srinivasan, Venkiteshwar Manoj Clinical Development and Medical Affairs, Alcon Research, LLC, Johns Creek, GA, USACorrespondence: Sruthi SrinivasanClinical Development and Medical Affairs, Alcon Research, LLC, 11460 Johns Creek Parkway, Johns Creek, GA, 30097, USATel +1 678 415-5315Email sruthi.srinivasan@alcon.comAbstract: Dry eye disease (DED) is a multifactorial ocular condition characterized by a loss of homeostasis of the tear film resulting in ocular symptoms of discomfort, irritation, and visual disturbance, all of which significantly impact the patients’ social and occupational quality of life. While management of DED depends on the severity of symptoms and signs, use of artificial tear products (ATPs) that replace or supplement the deficient natural tear film is the mainstay treatment option. In this review, we present a decade of evidence on Systane Ultra® (polyethylene glycol [PEG]/propylene glycol [PG] with hydroxypropyl guar [HP guar]) in effectively managing DED. The active demulcents in Systane Ultra®—PEG, PG, along with HP guar gelling technology—provide optimal ocular surface protection and lubrication to heal damaged areas of the cornea caused by DED and, therefore, are recommended for patients with both aqueous and/or mucin layer deficiencies. Over the years, several clinical studies have shown that PEG/PG with HP guar provides long-lasting relief from dry eye and has often been chosen as a standard or comparator against other ATPs. Here, we describe the salient features of PEG/PG with HP guar—its constituents and their mechanisms of action. Furthermore, we summarize results from a systematic literature search that identified 23 relevant publications further emphasizing on the effectiveness and safety of PEG/PG with HP guar in alleviating the signs and symptoms of DED.Keywords: artificial tear products, dry eye disease, PEG/PG with HP guar